The effect of sulfur vapor pressure on Cu2ZnSnS4 thin film growth for solar cells. (15th May 2017) - Wang, Weihuang; Wang, Guohui; Chen, Guilin; Chen, Shuiyuan; Huang, Zhigao
Highlights: Study the properties and the device performance of CZTS annealed under various sulfur vapor pressure. Offered an available and useful information for further development of CZTS absorber materials. Providing a valid platform for feasible control of the sulfur vapor pressure compared to high toxic H2 S gas. A champion PCE (2.59%) of CZTS was obtained under sulfur vapor pressure. Abstract: The sulfurization is an essential process during the preparation of high quality Cu2 ZnSnS4 (CZTS) absorber layers, which is controlled by the parameters such as annealing time, temperature and atmosphere, etc. The heat under different temperature not only provides energy for the samples, but also determines the sulfur vapor pressure, which affects the CZTS growth. To distinguish the effect of energy supply and sulfur vapor pressure on CZTS films, a two-temperature zone tube furnace was used, which permits independent control of the sulfur source and substrate temperature. Keeping the substrate temperature constant, the morphology and crystalline of CZTS thin films were investigated under various sulfur vapor pressure by changing sulfur temperature. Finally, the device performances have also been studied, which depended significantly on the sulfur vapor pressure. A champion PCE (2.59%) of oxide-derived CZTS device was obtained under high sulfur vapor pressure.